Synthesys and Characterization of Silver-doped Hydroxyapatite - PETKES, Regina; FARKAS, Noémi-Izabella; MARINCAȘ, Laura; BARTHA-VARI, Judith-Hajnal; BARABÁS, Réka (Studia Universitatis Babeș-Bolyai Chemia, 2023)
Different preparation methods of Ag-doped hydroxyapatite were compared and an efficient solid-state reaction-based method was developed for the synthesis of silver doped-hydroxyapatite using AgNO3 as silver source. The obtained nanomaterial was characterized by SEM, EDS and XRD measurements. By this method 10% silver was detected in the structure of the hydroxyapatite.